Cardiac Tuberculoma Presenting as Sudden Cardiac Death in an Immunocompetent Young Man: A Case Report and Literature Review - Alemayehu Shiferaw Lema (Case Reports in Cardiology)
Tuberculosis is one of several preventable and curable communicable diseases that is a major cause of morbidity and one of the top ten causes of death worldwide. Cardiac tuberculosis frequently affects the pericardium. Although rare, most cases of tuberculosis involving the myocardium and endocardium present as sudden cardiac death in asymptomatic cases. Information about the myocardial involvement of tuberculosis appears in the literature once in a blue moon. As a result, there is a knowledge gap about cardiac tuberculosis among health professionals. Here, a case of sudden cardiac death from tuberculoma of the right atrium with a secondary thrombus causing bicaval obstruction that is observed in an asymptomatic immunocompetent young man is presented. Furthermore, challenges related to the diagnosis and management of cardiac tuberculosis are discussed, and an overview of the relevant literature is provided to break new ground in early diagnosis and therapy.